Economic Development and Economic Governance Through the Example of the City of Győr - Dávid Fekete (DETUROPE)
Since the 1990s the metropolitan region and its governance has got into the focus of regional science again. Nowadays a newer wave of metropolitan governance is authoritative, which has exceeded the former administrative-territorial planning aspects, and has appeared on the scene as the mechanism of economic development policy. Examining the development stages of regional policy it is well-known that the classical (modern) approach was superseded by the postmodern one. While the national methods applied in the classical period were characterized by strictness, central regulation, indirect regulation of the market (Fordist approach), in the postmodern period flexibility, decentralization and direct regulation have come to the fore (Post-Fordism). In the postmodern period the state level also takes its role in the financing of innovation and research&development, and the notions of networking and competitiveness are coming more and more to the fore. In this article I analyze these processes through the case study of Győr. After the theoretical introduction I examine the tools of economic development and economic governance in the Győr metropolitan region. Activities observed in Győr can strengthen the view-point that the processes of economic development and economic governance have nowadays been going on in parallel with each other. Moreover, the coordinating activities of local authorities can be observed in the work of organizations that support economic governance. In the course of the research it was also confirmed that built infrastructure can serve as a fundamental condition for the cooperation of network-systems that operate the governance system of a municipality.